CCCDTD5 recommendations on early and timely assessment of neurocognitive disorders using cognitive, behavioral, and functional scales. Issue 1 (11th November 2020) - Tang‐Wai, David F.; Smith, Eric E.; Bruneau, Marie‐Andrée; Burhan, Amer M.; Chatterjee, Atri; Chertkow, Howard; Choudhury, Samira; Dorri, Ehsan; Ducharme, Simon; Fischer, Corinne E.; Ghodasara, Sheena; Herrmann, Nathan; et al.
Abstract: Introduction: Earlier diagnosis of neurocognitive disorders and neurodegenerative disease is needed to implement preventative interventions, minimize harm, and reduce risk of exploitation in the context of undetected disease. Along the spectrum from subjective cognitive decline (SCD) to dementia, evidence continues to emerge with respect to detection, staging, and monitoring. Updates to previous guidelines are required for clinical practice. Methods: A subcommittee of the 5th Canadian Consensus Conference on Diagnosis and Treatment of Dementia (CCCDTD) reviewed emerging evidence to address the following: (1) Is there a role for screening at‐risk patients without clinical concerns? In what context is assessment for dementia appropriate? (2) What tools can be used to evaluate patients in whom cognitive decline is suspected? (3) What important information can be gained from an informant, using which measures? (4) What instruments can be used to get more in‐depth information to diagnose mild cognitive impairment (MCI) or dementia? (5) What is the approach to those with cognitive concerns but without objective changes (ie, SCD)? (6) How do we track response to treatment and change over time? The Grading of Recommendations Assessment, Development, and Evaluation system was used to rate quality of the evidence and strength of the recommendations. Results: We recommend instruments to assess and monitor cognition, behavior, and function across the cognitive spectrum, including reports from patient and informant. We recommend against screening asymptomatic older adults but recommend investigation for self‐ or informant reports of changes in cognition, emergence of behavioral or psychiatric symptoms, or decline in function or self‐care. Standardized assessments should be used for cognitive and behavioral change that have sufficient validity for use in clinical practice. Discussion: The CCCDTD5 provides evidence‐based recommendations for detection, assessment, and monitoring of neurocognitive disorders. Although these guidelines were developed for use in Canada, they may also be useful in other jurisdictions.